Investigating a suitable model for the study of vitamin D mediated regulation of human placental gene expression. Issue 199 (May 2020) - Simner, Claire L.; Ashley, Brogan; Cooper, Cyrus; Harvey, Nicholas C.; Lewis, Rohan M.; Cleal, Jane K.
Highlights: Placental transfer and metabolism of vitamin D are not well understood: model systems are needed to help understand these. BeWo cells and HEK293 cells were investigated as a model to study effects of vitamin D on placenta gene expression. Expression of key amino acid transporters was similar in HEK293 and lower in BeWo cells compared to placenta Expression of vital vitamin D related genes was not detected in BeWo cells. Culture of HEK293 cells with 1, 25(OH)2 D showed no effects on nutrient transporter expression. Abstract: Transfer and metabolism of vitamin D across the human placenta is required for fetal development. However, these fundamental mechanisms are not well understood and model systems are required to help understand them. The BeWo choriocarcinoma cell line is derived from extravillous trophoblast but is used as a model for villous syncytiotrophoblast and the placental barrier. Questions have been raised about the suitability of the BeWo cell line as a model for villous trophoblast. This study compares the expression of amino acid transporters and vitamin D related genes in human term placenta with the BeWo and human embryonic kidney (HEK)293 cell lines. HEK293 cells, as transporting epithelium may be more similar to placenta. Gene expression in term placenta was much more similar to HEK293 than BeWo. This study provides further evidence that the BeWo cell line is not an appropriate model for villous trophoblast and a model that more closely represents the human placenta is now required to investigate the effects of vitamin D on the placenta ex-vivo .